2014
DOI: 10.12980/apjtb.4.2014b85
|View full text |Cite
|
Sign up to set email alerts
|

Multi–antibiotic resistant bacteria in frozen food (ready to cook food) of animal origin sold in Dhaka, Bangladesh

Abstract: This type of frozen food contaminated with multi-antibiotic resistant microorganisms can be potential vehicles for transmitting food-borne diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 10 publications
3
22
0
3
Order By: Relevance
“…Enteric fever cases have occurred throughout the study period which implied that safety of drinking water hygienic practice and sanitation have not improved much over that period. In our study period, only 18.85% showed growth which is similar to the results done by Masoumi et al and Sultana et al[21,22]. There is direct relationship between the volume of blood obtained and the yield of a blood culture (University of Pennsylvania Medical Center Guidelines for Antibiotic Use, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Enteric fever cases have occurred throughout the study period which implied that safety of drinking water hygienic practice and sanitation have not improved much over that period. In our study period, only 18.85% showed growth which is similar to the results done by Masoumi et al and Sultana et al[21,22]. There is direct relationship between the volume of blood obtained and the yield of a blood culture (University of Pennsylvania Medical Center Guidelines for Antibiotic Use, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Lack of growth in blood culture during isolation of pathogen is common, most probably, due to the use of antibiotics prior to blood collection for culture. Availability and misuse of antibiotics even for mild cases of fever is common in Nepal [22]. A relation between antibiotic use and its resistance in clinical isolates had been proven in more studies.…”
Section: Discussionmentioning
confidence: 99%
“…We isolated S. aureus from 76.47% of chicken meat. Previous studies conducted in Bangladesh reported a wide range of S. aureus prevalence in chicken meat which varied from 24.56-95.83% (Islam et al, 2014;Datta et al, 2012;Sultana et al, 2014 andAndrew et al, 2011). This variation in prevalence with our findings might be due to the variation in the type of sample (Andrew et al, 2011) like raw and frozen sample.…”
Section: Discussionmentioning
confidence: 97%
“…55 An evaluation in Poland of the resistant profile of Staphylococcus spp. isolated from 858 RTE foods (cheeses, cured meats, sausages, smoked fish, salads) found that 54.9% of the isolates were resistant to at least one class of antibiotics, and, of these, 35.4% of the strains were multidrug resistant, suggesting that RTE food is an important route for the transmission of resistant bacteria.…”
Section: Bacteria In the Food Chainmentioning
confidence: 99%